2007
DOI: 10.1080/00016480601110238
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relation between human papilloma virus and larynx cancer

Abstract: Human papilloma virus (HPV) has a role in benign and malignant pathology of the larynx. In this review we present the biological and epidemiological aspects related to these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…8,9 Polymerase chain reaction (PCR) studies of these lesions have identified benign HPV DNA at an average rate of 76.2%. 10 To date, most reports have focused on larger, invasive carcinomas, and few studies have explored the role of HPV in the cellular changes that precede malignancy or occur during the early stages of transformation.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Polymerase chain reaction (PCR) studies of these lesions have identified benign HPV DNA at an average rate of 76.2%. 10 To date, most reports have focused on larger, invasive carcinomas, and few studies have explored the role of HPV in the cellular changes that precede malignancy or occur during the early stages of transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to anogenital SCC, the prevalence of HPV in laryngeal SCC varies considerably, from 3 to 60 % [38,39]. Li and co-workers [40] recently published a meta-analysis with 55 studies, addressing HPV prevalence in laryngeal SCC.…”
Section: Important Differences Between Cervical and Head And Neck Silsmentioning
confidence: 99%
“…The detection of HPV DNA in premalignant lesions shows that HPV infection can be involved in the development of some lesions. Premalignant oral lesions usually develop as a result of several factors, such as tobacco and alcohol, and the synergistic interaction of HPV infection with these factors may play a role in the progression to cancer (Torrente & Ojeda, 2007). However, although HPV has been found in a large proportion of laryngeal cancers, more epidemiological and experimental studies are needed to clarify the role of HPV in laryngeal carcinomas.…”
Section: Hpv In Laryngeal Cancermentioning
confidence: 99%
“…According to the clinical characteristics and natural history of disease, four different forms of laryngeal papillomas exist, namely isolated juvenile papillomatosis, juvenile multiple, adult and adult isolated multiple (Madkan et al 2007;Torrente & Ojeda, 2007). More recently, this nomenclature has been replaced by recurrent respiratory papillomatosis (RRP), which more accurately describes the extent of the disease and its tendency to recur (Muenscher et al, 2008).…”
Section: Hpv In Laryngeal Cancermentioning
confidence: 99%
See 1 more Smart Citation